2020
DOI: 10.9734/jaeri/2020/v21i530145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prevalence and Incidence of Sesame Gall Midge (Asphondylia sesami Felt) in Kafta-Humera District Tigray, Ethiopia

Abstract: Gall midge (Asphondilia sesame Felt) is one of the most serious insect pests of sesame threatening sesame production in Tigray, Ethiopia. The aim of the present study was to assess distribution and incidence of sesame gall midge and its association with different agronomic practices. Field survey was conducted in Kafta-Humera, districts in 2019 cropping season. A total of 60 farmers’ fields were assessed for the prevalence and incidence of the insect. Results indicated that 94% of farmers’ fields were infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Depletion of the soil and reduced nutrient recycling, high pest incidence, and disease infestation are some of the problems of mono-cropping (Ehrmann & Ritz, 2014;Heggenstaller et al, 2008;Mugi-Ngenga et al, 2022). Kebede et al (2020) & Kindeya (2018) also indicated that low crop diversity in the sesame growing areas has resulted in high disease infestation.…”
Section: Sustainability Of the Sesame Value Chaincontinuity Of Produc...mentioning
confidence: 99%
“…Depletion of the soil and reduced nutrient recycling, high pest incidence, and disease infestation are some of the problems of mono-cropping (Ehrmann & Ritz, 2014;Heggenstaller et al, 2008;Mugi-Ngenga et al, 2022). Kebede et al (2020) & Kindeya (2018) also indicated that low crop diversity in the sesame growing areas has resulted in high disease infestation.…”
Section: Sustainability Of the Sesame Value Chaincontinuity Of Produc...mentioning
confidence: 99%